Emerging Discourses on Freedom of Religion or Belief in Indonesia - Bagir, Zainal Abidin ca. 20./21. Jh. (Interreligious studies and intercultural theology, 2022)
The notion of religious freedom has existed since the founding of an independent Indonesia in 1945, but it took on a more prominent and effective profile only after the democratization that started in 1998. While the discourse has been dominated by discussion of the normative legal dimensions and lack of effective implementation that led to certain violations of the rights to FORB, it has recently expanded to deeper, more foundational questions and touched on more theoretical issues. This article considers three relevant developments that constitute the context: the legal landscape, advocacy, and the emerging conceptual discourses. It then positions the three issues discussed in the following three articles. Acknowledging that the three issues do not exhaust the whole landscape of FORB discourses in Indonesia, this article concludes by mentioning a few other issues that deserve attention and suggests discussing them as part of the international discourse on FORB.